Italy : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
There is broad agreement on the appropriateness of the budget deficit target. The government aims to strengthen expenditure control and efficiency, at the national and at subnational levels, to achieve a reduction in the tax burden while cutting the fiscal deficit. The IMF staff suggested complementing new initiatives, aimed at strengthening growth prospects in the South, with strong labor market measures. Continued wage moderation, a reduction in the tax burden, and further product market reform and privatization will help secure an adequate level of competitiveness.